Penyuluhan masyarakat dalam upaya peningkatan pengetahuan mengenai malaria dan nyamuk vektor malaria serta screening dini malaria di Kelurahan Kemelak RT 01 Kabupaten Baturaja - Azhari, Dalilah; Susilawati, Susilawati; Handayani, Dwi; Prasasty, Gita Dwi; Amalia, Ella; Pariyana, Pariyana; Theresy, Elzabet; Irnanda, Andi (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Malaria is caused by a parasite of the genus Plasmodium that is transmitted to humans through the bite of a female Anopheles mosquito. Indonesia is the second highest ranked region in Asia with 214 regencies/cities in Indonesia that are still malaria endemic spread from Sumatra to Papua. Knowledge is one of the important components in preventing malaria transmission. The purpose of this service was to assist and screen for malaria in the context of early detection of malaria in the community and to increase public knowledge about malaria and malaria mosquito vectors. Activities were carried out by providing pretests followed by education and socialization of malaria and early screening of malaria cases with Rapid Diagnostic Test (RDT) examination. Education and socialization events were held at RT 01 Kemelak Baturaja using LCD projector media as well as posters and pamphlets. A total of 83 people attended the counseling event consisting of 37 men and 46 women and 50 people carried out early detection of malaria RDT examination. Pretest results obtained knowledge that was still lacking in knowledge of malaria and malaria vectors by 78% and good knowledge by 22%. There was an increase in knowledge in the posttest held after counseling and education where lack of knowledge was 44% and good knowledge to 56%. On examination with RDT found no positive cases of malaria. Education and socialization in the community about the symptoms of malaria and its vectors can increase awareness of the disease and prevent malaria vector mosquito bites. Therefore, education and assistance are an important part of efforts to prevent and reduce cases that support malaria elimination.